Análisis del potencial del turismo termal en el cantón Urcuquí - Arciniega Echeverría, Camila Salomé (2022)
Urcuquí has a great potential for tourism as it has thermal waters of volcanic origin that are beneficial for health, some studies have proven the healing power for ailments and some rheumatic diseases, also the hot springs are visited by tourists for rest, relaxation, among others. That is why this study proposes to analyze the potential of the thermalism within the locality proposing several strategies so that the thermalism can be developed in a great way. The methodology carried out is based on two approaches, qualitative and quantitative, that is to say, it is mixed research, which is accompanied by two research methods, analytical synthetic and deductive\; in the same way, three research techniques are added: observation, interviews and surveys. Thus, a non-probabilistic sample of convenience was applied to a universe of 100 tourists that arrive to the different thermal spas of the Urcuquí canton. In the results, relevant information was obtained about the current situation of the area where these establishments are located, as well as the reason why visitors come to the locality and the relevance generated by these waters. In this way, the strategies to strengthen the thermal tourism were established, concluding that the thermalism within the locality of Urcuquí has been developed and strengthened over the years.